Discussion Club “Cui Prodest?” - Tkacheva, Marina (project baikal, 2017)
The discussion is focused on the analysis of the design and construction practices in Irkutsk and the Irkutsk region. It raises the question of advantages / drawbacks of transformation of the urban environment depending on the policy of regional authorities and developers. The participants of the discussion review the problems concerning the colouristic environment of the city, protection of the architectural heritage, downtown density, as well as the change in perception of the city in light of the popularity of the 130 Quarter.
Keywords: architecture; city; architectural environment; policy; authoritative will; social stratification; development; 130 Quarter